THE METHODOLOGICAL POTENTIAL OF INDUSTRIAL PRODUCTION AS THE BASIS OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS - Evgeny A. Korchagin; Rais S. Safin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article describes the methodological potential of industrial production in the aspect of professional training of future specialists. As structural components of the potential, three methodological points are indicated: technology as an integration component of the production process; the integration of science, education and production; the priority of occupational and professional values and goals in the professional development of the personality of the future specialist. According to the methodological data, it is suggested to look on integrity training and production process as coordinated interaction of the educational process at university and the production process in an industrial plant is proposed. The fundamental difference between training and production process from the conventional one, is that knowledge, skills, and competences are formed within the context of development of a complex and dynamic system of professional activity and thinking of the specialist. Under the conditions of market economy and competition in the market of goods and services methodological basis of training is to be the training of future specialists to work under the changing conditions of practical activities. Thus, the focal point is displaced from the formation of students' knowledge, skills, competencies to the mastering of the art of their application in accordance with production needs.